Distribusi Dan Kondisi Pada Vegetasi Padang Lamun di Biak Padaido, Papua - Amanda, Raditya Andrea Kristian; Luthfi, Oktiyas Muzaky (Universitas Bangka Belitung, 2024)
Seagrass beds are an ecosystem in coastal areas that have a fairly high level of biodiversity and are potential contributors of nutrients to the surrounding waters because they have a high level of productivity. In this research we will find out about seagrass cover in Padaido and Biak, Papua. The results of monitoring carried out in 2018 took 8 points in Biak waters. Station 7 has the highest percentage of seagrass cover at 80.86% (very dense category) which has a percentage value of 76-100% (healthy seagrass meadow status). Results of monitoring carried out in 2019 at 8 water points on Padadido Island. Station 3 has the highest percentage of seagrass cover at 66.48% (very dense category) which has a percentage value of 76-100% (healthy seagrass meadow status). Of the 16 species found in Indonesia, there are 5 types of species found in the waters of Biak, Papua, namely, Enhalus acoroides, Thalassia hemprichii, Cymodocea rotundata, Haludole pinifolia, Halophila ovalis, and Syringodium iseotifolium. Just like at Biak Station, Padaido Station itself found 8 types of species in Papuan waters, namely, Enhalus acoroides, Thalassia hemprichii, Cymodocea rotundata, Cymodocea serrulata, Haludole pinifolia, Halodule uninervis, Halophila ovalis, and Syringodium iseotifolium.